Carbon Stock Dinamics of Gmelina (Gmellina arborea Roxb.) based Agroforestry in Private Forest, Tasikmalaya and Banjar District, West Java - Siarudin, Mohamad Siarudin; Yonky , Yonky Indrajaya (Forestry Department, University of Muhammadiyah Makassar, 2017)
This research aims at measuring carbon (C) stock of gmelina (Gmelina arborea Roxb.) agroforestry system and its carbon diynamics due to several harvesting rotations. Observation was conducted during March – October 2014, on 17 plots in private forest, located in Tasikmalaya and Banjar District, West Java Province. The C-stock measurement followed Rapid Carbon Stock Appraisal Method (RaCSA) with some additional analysis. The dynamic of C-stock was measured based on biological rotation, technical rotation-1 (harvesting at tree diameter of 15 cm) and technical rotation-2 (harvesting at tree diameter of 20 cm). The result of the study shows that average of C-stock in gmelina agroforest stand is 170 ton/ha, consisted of 64 ton/ha above ground C and 106 ton/ha below ground C. Biological rotation (8 years) results in maximum C-stock of 15 ton/ha at harvesting time, while the time averaged-C stock is 7 ton/ha/year.Technical rotation-1(14 years) and technical rotation-2 (24 years) result in maximum C-stock of 23 ton/ha and 28 ton/ha respectively, while the time averaged-C-stock are 12 ton/ha/year and 18 ton/ha/year respectively.